ANALISIS UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK TERKAIT FUNGSI PENDIDIKAN POLITIK GUNA MENCEGAH PRAKTIK KORUPSI - Karuniasa, Nanda Pramesti; Maharani, Andina Elok Puri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
The writing of this law aims to examine the regulation of political education based on Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties and to know the ideal and efficient arrangements of political education to prevent corrupt practices. Because one of the functions of political parties is a functions of political education so as to create popular sovereignty political parties need to carry out their functions, namely political educations. This legal research uses descriptive normative research. The approach taken is through the statutory approach and conceptual approach. Sources of legal materials consist of primary legal materials and secondary legal materials. While the legal material collection techniques used are library studies and Cyber Media and analysis of legal materials in legal research is carried out using the deduction method.